Low-temperature cured two-component epoxy resin conductive adhesive and preparation method thereof
By using phenolic epoxy resin in the conductive adhesive, mixing traditional epoxy resin and core-shell toughening epoxy resin, combined with modified amine-based curing agent and phenol-based accelerator, a two-component epoxy resin conductive adhesive is formed, which solves the problem that low-temperature curing conductive adhesive is difficult to meet the mechanical strength and conductivity at the same time, and achieves a high-performance low-temperature curing effect.
Patent Information
- Application Number
- CN202411878604.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, low-temperature cured conductive adhesives are difficult to meet the requirements of mechanical strength and conductivity at the same time, and the reduction of curing temperature often leads to high production costs and reduced performance.
Using a two-component epoxy resin conductive adhesive, the mixture of phenolic epoxy resin and traditional epoxy resin and core-shell toughened epoxy resin is combined with a modified amine-based curing agent and a phenol-based accelerator to form component A and component B mixed curing at room temperature 1:1.
It realizes the conductive adhesive cured under low temperature conditions, has good mechanical properties and conductive properties, has short curing time, low volume resistivity, high bonding strength, high environmental reliability, and can maintain stable performance after hot and cold cycle impact and aging.
Smart Images

Figure CN119592276A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of conductive adhesives, and in particular to a low-temperature curing two-component epoxy resin conductive adhesive and a preparation method thereof. Background Art
[0002] Conductive silver glue is an adhesive material for electronic products that has certain conductive properties after curing or drying. It is used for packaging and bonding electronic components and assemblies such as liquid crystal displays, light-emitting diodes, integrated circuit chips, and printed circuit board assemblies. According to different curing systems, conductive glue can be divided into room temperature curing conductive glue, medium temperature curing conductive glue, high temperature curing conductive glue, and ultraviolet light curing conductive glue.
[0003] Most of the conductive silver glues currently available on the market are medium-temperature curing conductive glues. The conductive glues have excellent mechanical properties, and the curing temperature is generally below 150°C. This temperature range can better match the operating temperature and heat resistance of electronic components, so it is the most widely used conductive glue at present. However, in situations such as bottom filling protection and reinforcement in chip packaging, bonding and fixing protection of light sources of LED lamp beads, and fixed sealing and confidentiality protection of heat-sensitive circuit board components in the circuit board field, a large amount of low-temperature curable conductive glue is still needed. Therefore, it is particularly necessary to study a conductive silver glue that can be cured under low-temperature conditions to solve problems such as the inability of electronic components to withstand high temperatures.
[0004] In order to reduce the curing temperature of the conductive silver glue, more curing agent or curing agent that reacts more strongly with the matrix is often added, resulting in a decrease in the conductivity of the matrix. In order to improve its conductivity, more conductive fillers are added, which further reduces the adhesion and toughness of the matrix. That is, low-temperature curing is often difficult to coexist with the improvement of electrical and mechanical properties. For example, Chinese patent CN102399523A discloses a conductive silver glue that is filled with nano-silver and cured at room temperature and is resistant to high temperatures, which can improve its conductivity. However, the silver nanowire process is not only complicated and cumbersome, but also has a high preparation cost. And due to the curing reaction temperature, the cross-linking density of the resin is low, and since the mechanical properties are mainly affected by the degree of partial reaction of the resin matrix, it is easy to cause the mechanical properties of the product to decrease. Summary of the invention
[0005] The object of the present invention is to provide a low-temperature curing two-component epoxy resin conductive adhesive and a preparation method thereof, so as to solve the technical problems in the prior art that the curing temperature decreases and the mechanical strength and conductive properties of the colloid after curing cannot be satisfied at the same time.
[0006] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0007] The present invention provides a low-temperature curing two-component epoxy resin conductive adhesive, comprising:
[0008] Component A and component B, wherein the component A and the component B are mixed in a ratio of 1:1 and then cured at room temperature;
[0009] The component A contains at least the following components in parts by mass: 3-6 parts of phenolic epoxy resin, 2-5 parts of epoxy resin, 1-5 parts of core-shell toughened epoxy resin, 3-6 parts of diluent, 0.10-0.20 parts of coupling agent, 0.1-0.5 parts of thixotropic agent, and 75-85 parts of conductive filler;
[0010] The B component contains at least the following components in parts by mass: 3 to 8 parts of a curing agent and 0.5 to 1.0 parts of an accelerator;
[0011] Wherein, the core-shell toughened epoxy resin is a bisphenol A type epoxy resin with uniform nano-scale core-shell particle dispersion.
[0012] As a preferred solution of the present invention, the phenolic epoxy resin is EPALLOY-8240, and the epoxy value is 0.57-0.61.
[0013] As a preferred embodiment of the present invention, the epoxy resin is any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and aliphatic epoxy resin, and the epoxy value is 0.40-0.65.
[0014] As a preferred embodiment of the present invention, the core-shell toughened epoxy resin is any one or more of EPX-125, EPX-152, and EPX-252.
[0015] As a preferred embodiment of the present invention, the diluent is a mixture of an active diluent and an inactive diluent;
[0016] Wherein, the active diluent is any one or more of p-tert-butylphenyl glycidyl ether, cyclohexyl dimethanol diglycidyl ether, and trimethylolethane triglycidyl ether;
[0017] The inactive diluent is any one or more of divalent acid ester, terpineol and benzyl alcohol.
[0018] As a preferred embodiment of the present invention, the coupling agent is any one or more of silane coupling agents.
[0019] As a preferred embodiment of the present invention, the conductive filler includes flaky silver powder and spherical silver powder;
[0020] Wherein, the particle size of the flaky silver powder is 1-5 μm, 5-10 μm and 10-15 μm;
[0021] The particle sizes of the spherical silver powder are 1-5 μm, 5-10 μm and 10-15 μm.
[0022] As a preferred embodiment of the present invention, the thixotropic agent is fumed silica.
[0023] As a preferred embodiment of the present invention, the curing agent is any one or more of the modified amine curing agents EH-451K, HD-2520, and HD-2588;
[0024] The accelerator is any one or more of DMP-30 and HD-1022.
[0025] The present invention also provides a method for preparing a low-temperature curing two-component epoxy resin conductive adhesive, comprising the following steps:
[0026] The phenolic epoxy resin, the epoxy resin and the core-shell toughened epoxy resin are mixed evenly, and a vacuum device is used to perform a degassing treatment to obtain a mixed resin;
[0027] In a grinding state, sequentially adding the thixotropic agent, the diluent, the coupling agent and the conductive filler to the mixed resin, mixing and grinding them to make them fully mixed and uniform, to obtain a first organic carrier;
[0028] Grinding the first organic carrier to a fineness of 10-30 μm using a three-roll mill to obtain the A component;
[0029] The curing agent and the accelerator are mixed and ground to be fully mixed, and a vacuum device is used to perform a degassing treatment and then the grinding is continued to obtain a second organic carrier;
[0030] The second organic carrier is ground to a fineness of 10-30 um using a three-roll mill to obtain the B component.
[0031] As a preferred solution of the present invention, a three-roll mill is used to grind the first organic carrier to a fineness of 20 um.
[0032] As a preferred solution of the present invention, a three-roll mill is used to grind the second organic carrier to a fineness of 20 um.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention uses a phenolic epoxy resin mixed with a traditional epoxy resin and a core-shell toughened epoxy resin as a resin matrix. The core-shell toughened epoxy resin is a bisphenol A type epoxy resin with uniform nano-scale core-shell particle dispersion, which replaces the traditional nitrile rubber. The phenolic epoxy resin has low viscosity and good temperature resistance. The core-shell toughened epoxy resin is a stable translucent core-shell particle dispersion, which can effectively increase the shear strength and tear strength of the cured product and improve the toughness of the cured product, so that the cured product still has good toughness, that is, good mechanical properties, while having a large amount of conductive fillers to ensure its conductive performance.
[0035] The present invention ensures that when the adhesive is cured at a low temperature, the resin matrix part has a high degree of reaction, the conductive path of the conductive particles is unobstructed, and the adhesive has good toughness and strength after curing. Compared with commercially available low-temperature curing conductive silver glue products, the low-temperature conductive silver glue of the present invention has simple curing time conditions, lower volume resistivity, higher bonding strength, high environmental reliability, and better toughness. At -55°C to 125°C, after multiple hot and cold cycle shocks, the volume resistivity and bonding strength of the sample do not change significantly, and the adhesive has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0037] Figure 1 The present invention provides a schematic flow chart of a method for preparing a low-temperature curing two-component epoxy resin conductive adhesive. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention provides a low-temperature curing two-component epoxy resin conductive adhesive. The adhesive is divided into a component A and a component B. The two-component adhesives are stored separately before use. When in use, the component A and the component B are mixed in a ratio of 1:1. After mixing together, the components are quickly injected into the use position. The adhesive can be cured at room temperature.
[0040] In this embodiment, component A contains at least the following components, measured by mass: 3 to 6 parts of phenolic epoxy resin, 2 to 5 parts of epoxy resin, 1 to 5 parts of core-shell toughened epoxy resin, 3 to 6 parts of diluent, 0.10 to 0.20 parts of coupling agent, 0.1 to 0.5 parts of thixotropic agent, and 75 to 85 parts of conductive filler.
[0041] Calculated by weight, component B contains at least the following components: 3 to 8 parts of a curing agent and 0.5 to 1.0 parts of an accelerator, wherein the curing agent is a modified amine curing agent.
[0042] Component A is the key to ensure that the adhesive still has good mechanical properties when cured at low temperatures. Phenolic epoxy resin is mixed with traditional epoxy resin and core-shell toughened epoxy resin as the resin matrix to give the conductive silver glue good mechanical properties when reacting at lower temperatures, so that the adhesive has good toughness and strength after curing.
[0043] Furthermore, the core-shell toughened epoxy resin in component A replaces the traditional nitrile rubber. The core-shell toughened epoxy resin is a bisphenol A type epoxy resin with uniform nano-scale core-shell particle dispersion. The phenolic epoxy resin has low viscosity and good temperature resistance. The core-shell toughened epoxy resin, as a stable translucent core-shell particle dispersion, can effectively increase the shear strength and tear strength of the cured product and improve the toughness of the cured product, so that it still has good toughness, that is, good mechanical properties, while having a large amount of conductive fillers to ensure its conductive properties.
[0044] At the same time, the present invention improves the usage ratio of resins, explores the influence of the interaction between phenolic epoxy resin and core-shell toughened epoxy resin, and prepares conductive silver glue according to formulas with different ratios by adjusting the matching ratio of different epoxy resins and the mutual coordination with amine curing agents. The influence of different ratios of epoxy resin on the comprehensive performance of high-performance, low-temperature cured conductive silver glue is compared, and the appropriate ratio range is determined for application.
[0045] Compared with commercially available low-temperature curing conductive silver paste products, the low-temperature conductive silver paste of the present invention has a short curing time, a high degree of reaction of the resin matrix, and a lower volume resistivity; at the same time, due to the high degree of reaction of the resin matrix, the bonding strength is higher, the environmental reliability is high, and it has better toughness. At -55°C to 125°C, after multiple hot and cold cycle shocks, the volume resistivity and bonding strength of the sample do not change significantly.
[0046] Among the above components, the phenolic epoxy resin can be selected in any range, but in order to improve the toughness of the colloid, the phenolic epoxy resin in this embodiment is EPALLOY-8240, and the epoxy value is 0.57-0.61.
[0047] Among the above components, the epoxy resin can be selected within any range, but in order to improve the toughness of the colloid, the epoxy resin in this embodiment is any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and aliphatic epoxy resin, and the epoxy value is 0.40-0.65.
[0048] Among the above components, the core-shell toughened epoxy resin can be selected in any range. The core-shell toughened epoxy resin has good impact resistance and heat resistance and good compatibility with other epoxy resins. However, in order to improve the toughness of the colloid, the core-shell toughened epoxy resin in this embodiment is any one or more of EPX-125, EPX-152, and EPX-252 provided by Shanghai Luohe High-tech Materials Co., Ltd.
[0049] Among the above components, the diluent can be selected in any range, but in order to improve the toughness of the colloid while having excellent conductive properties, the diluent in this embodiment is a mixture of an active diluent and an inactive diluent. The use of a certain proportion of the inactive and active diluents can effectively reduce the viscosity of the system and facilitate the uniform dispersion of the conductive filler, thereby ensuring the conductive properties of the conductive silver paste to a certain extent.
[0050] Preferably, the active diluent is any one or more of p-tert-butylphenyl glycidyl ether, cyclohexyl dimethanol diglycidyl ether, and trimethylolethane triglycidyl ether.
[0051] Preferably, the inactive diluent is any one or more of divalent esters, terpineol, and benzyl alcohol.
[0052] Among the above components, the coupling agent can be selected in any range, but in order to improve the toughness of the colloid, in this embodiment, the coupling agent is any one or more of the silane coupling agents;
[0053] Among the above components, the thixotropic agent can be selected within any range, but in order to improve the toughness of the colloid, the thixotropic agent in this embodiment is fumed silica.
[0054] Among the above components, the conductive filler can be selected in any range, but in order to improve the toughness of the colloid, in this embodiment, the conductive filler includes flaky silver powder and spherical silver powder, the particle size of the flaky silver powder is 1-5μm, 5-10μm and 10-15μm, and the particle size of the spherical silver powder is 1-5μm, 5-10μm and 10-15μm. By mixing the different forms of spherical silver powder and flaky silver powder in a certain proportion, the density between the powders is increased, the conductive path of the silver powder is increased, and the conductive performance of the conductive silver glue is improved.
[0055] Among the above components, the curing agent can be selected within any range, but in order to maintain excellent performance of the colloid during low temperature curing, the curing agent in this embodiment is any one or more of the modified amine curing agents EH-451K, HD-2520, and HD-2588.
[0056] Among the above components, the accelerator can be selected within any range. However, in order to maintain excellent performance of the colloid during low temperature curing, the accelerator in this embodiment is any one or more of DMP-30 and HD-1022.
[0057] The present invention adopts a modified aliphatic amine curing agent and a phenol accelerator to cooperate. By using the modified aliphatic amine curing agent and the phenol accelerator to mix and match and adjust the ratio, the optimal reaction conditions and performance of low-temperature curing are determined. Compared with the conductive adhesive that is only suitable for room temperature curing at about 30°C and cannot be cured at different times within a certain temperature range at low temperature, this adhesive can be cured at different temperatures and can be cured at different times within a certain temperature range at low temperature, and has a wide range of uses.
[0058] like Figure 1 As shown, the present invention provides a method for preparing a low-temperature curing two-component epoxy resin conductive adhesive, comprising the following steps:
[0059] The phenolic epoxy resin, the epoxy resin and the core-shell toughened epoxy resin are mixed evenly, and a vacuum device is used to perform a degassing treatment to obtain a mixed resin;
[0060] In a grinding state, sequentially adding the thixotropic agent, the diluent, the coupling agent and the conductive filler to the mixed resin, mixing and grinding them to make them fully mixed and uniform, to obtain a first organic carrier;
[0061] Grinding the first organic carrier to a certain fineness using a three-roll mill to obtain the A component, wherein the fineness range is 10-30 um;
[0062] The curing agent and the accelerator are mixed and ground to be fully mixed, and a vacuum device is used to perform a degassing treatment and then the grinding is continued to obtain a second organic carrier;
[0063] The second organic carrier is ground to a certain fineness using a three-roll mill to obtain the B component, wherein the fineness ranges from 10 to 30 um.
[0064] The preparation method provided by the present invention mainly prepares conductive silver glue according to formulas of different proportions by adjusting the matching ratio of different epoxy resins and the mutual coordination with amine curing agents. The preparation process is simple and easy to operate. Adhesives with various properties can be obtained, and low-temperature curing performance as well as excellent conductive properties and mechanical properties can be ensured. The preparation method is simple and environmentally friendly, and can meet the needs of electronic adhesive operations in complex working environments, and has good practical value for industry development.
[0065] The following is further described through multiple embodiments:
[0066] Embodiment 1:
[0067] Take 4 parts of bisphenol A epoxy resin, 2 parts of p-tert-butylphenyl glycidyl ether, 2.5 parts of dibasic acid ester, 6.0 parts of HD-2588, 0.6 parts of DMP-30, 0.2 parts of silane coupling agent, 5 parts of EPALLOY-8240, 1.0 parts of EPX-125, 0.2 parts of fumed silica, and 80 parts of silver powder.
[0068] According to the above formula, EPALLOY-8240, bisphenol A epoxy resin and EPX-125 are uniformly mixed, and a vacuum machine is used for degassing to obtain a mixed resin;
[0069] In a grinding state, p-tert-butylphenyl glycidyl ether, dibasic acid ester, silane coupling agent, fumed silica and silver powder are sequentially added to the mixed resin, and the mixture is mixed and ground to be fully mixed and uniform, thereby obtaining a first organic carrier;
[0070] The first organic carrier is ground to 20 μm using a three-roll mill to obtain component A;
[0071] Mix HD-2588 and DMP-30 and grind them to make them fully mixed, use a vacuum machine to degas, and then continue grinding to obtain a second organic carrier;
[0072] The second organic vehicle was ground to 20 μm using a three-roll mill to obtain the B component.
[0073] Mix component A and component B together and characterize.
[0074] Embodiment 2:
[0075] Take 3 parts of EPALLOY-8240, 3.5 parts of bisphenol F epoxy resin, 1.5 parts of EPX-125, 2 parts of trimethylolethane triglycidyl ether, 2.5 parts of dibasic acid ester, 6.0 parts of EH-451K, 0.65 parts of DMP-30 and HD-1022 mixture, 0.15 parts of silane coupling agent, 0.2 parts of fumed silica, and 81 parts of silver powder.
[0076] According to the above formula, EPALLOY-8240, bisphenol F epoxy resin and EPX-125 are uniformly mixed, and a vacuum machine is used for degassing to obtain a mixed resin;
[0077] In a grinding state, trimethylolethane triglycidyl ether, dibasic acid ester, silane coupling agent, fumed silica and silver powder are sequentially added to the mixed resin, and the mixture is mixed and ground to be fully mixed to obtain a first organic carrier;
[0078] The first organic carrier is ground to 20 μm using a three-roll mill to obtain component A;
[0079] EH-451K, DMP-30 and HD-1022 were mixed and ground to be fully mixed, and then degassed using a vacuum machine and then ground again to obtain a second organic carrier;
[0080] The second organic vehicle was ground to 20 μm using a three-roll mill to obtain the B component.
[0081] Mix component A and component B together and characterize.
[0082] Embodiment 3:
[0083] Take 3 parts of EPALLOY-8240, 3.5 parts of a mixture of bisphenol F epoxy resin and bisphenol A epoxy resin, 1.2 parts of EPX-125, 5 parts of a mixture of cyclohexyl dimethanol diglycidyl ether and dibasic acid ester, 3.6 parts of a mixture of EH-451K and HD-2588, 0.5 parts of DMP-30, 0.1 parts of a silane coupling agent, 0.1 parts of fumed silica, and 83 parts of silver powder.
[0084] According to the above formula, EPALLOY-8240, bisphenol F epoxy resin + bisphenol A epoxy resin, and EPX-125 are uniformly mixed, and a vacuum machine is used for degassing to obtain a mixed resin;
[0085] In a grinding state, cyclohexyl dimethanol diglycidyl ether + dibasic acid ester, silane coupling agent, fumed silica and silver powder are sequentially added to the mixed resin, and the mixture is mixed and ground to be fully mixed and uniform to obtain a first organic carrier;
[0086] The first organic carrier is ground to 20 μm using a three-roll mill to obtain component A;
[0087] Mix EH-451K+HD-2588 and DMP-30 and grind them to make them fully mixed and uniform, use a vacuum machine to degas, and then continue grinding to obtain a second organic carrier;
[0088] The second organic vehicle was ground to 20 μm using a three-roll mill to obtain the B component.
[0089] Mix component A and component B together and characterize.
[0090] Test method:
[0091] 1. Volume resistivity: Use glass slides to prepare samples. The thickness of the two parallel tapes on the edge is 0.1mm. The slides are cleaned with ethanol and blown dry. Put an appropriate amount of conductive glue in the area between the two tapes, and squeeze the blade to obtain a long strip sample. There should be no wrinkles or bubbles on the surface of the sample after pasting. Use a special four-probe test fixture and milliohmmeter to measure the resistance. Place the four-probe fixture on the conductive glue sample at 25°C to ensure electrical contact between each probe and the material.
[0092] 2. Chip shear strength test:
[0093] The test was conducted at 25°C. The bonding strength test specimen used conductive silver glue as the adhesive and copper sheet as the substrate to bond 5 silicon-based chips. The bonding thickness was about 20μm. The applied force was measured and the type of failure (if failure occurred) produced by the force and the appearance of the remaining chip attachment material and the substrate metal layer were observed to determine the bonding strength of the conductive glue.
[0094] 3. Glass transition temperature test: Use a differential scanning calorimeter to conduct the experiment, heat up at a rate of 20°C / min and record. Perform a preheating cycle and perform a second temperature scan. According to the instrument's instructions, process the data to obtain the glass transition temperature.
[0095] 4. Hot and cold shock test: The experimental temperature is -50℃~85℃, the number of hot and cold shocks is 50 times, and the volume resistivity and chip shear strength of the sample are tested.
[0096] 5. Aging test: The experimental temperature is 50±2℃, the relative humidity is 95±5%, and the sample volume resistivity and bonding strength are tested for 24 hours.
[0097] 6. Temperature cycle experiment: The experimental temperature is -55℃~125℃, and the cycle is 100 times to test the sample volume resistivity and chip shear strength.
[0098] Test results:
[0099] The performance test results of Examples 1-3 are shown in Table 1 and Table 2:
[0100] Table 1
[0101]
[0102] Table 2
[0103]
[0104]
[0105] As can be seen from Table 1, Example 2 has more silver powder than Example 1, and its toughness should decrease accordingly. However, due to the increase in the ratio of the resin matrix and the high degree of reaction, its toughness increases instead. It can be seen that by mixing phenolic epoxy resin with traditional epoxy resin and core-shell toughened epoxy resin as the resin matrix, the conductive silver glue still has good mechanical properties when reacting at a lower temperature, so that the adhesive has good toughness and strength after curing.
[0106] As shown in Table 2, the room temperature curing conductive silver paste of the present invention not only has good volume resistivity, high shear strength and high glass transition temperature, but also can improve its mechanical properties while improving its conductive effect, and hot and cold shock has little effect on the volume resistivity and shear strength of the system.
[0107] After high temperature and high humidity aging, the volume resistivity and shear strength of the sample remained basically unchanged.
[0108] After the temperature cycling experiment, the volume resistivity and shear strength of the sample remained basically unchanged.
[0109] Through the low-temperature curing two-component epoxy resin conductive adhesive and its preparation method of this embodiment, the conductive adhesive can be cured at low temperature or room temperature, and the degree of reaction inside the matrix is high, while meeting its mechanical strength and conductive properties, and meeting the requirements of achieving effective bonding and maintaining good performance after curing of electronic components in application scenarios with use temperature requirements.
[0110] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present application. The protection scope of the present application is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present application within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present application.
Claims
1. A low temperature curing two-component epoxy resin conductive adhesive, characterized in that: include: Component A and component B, wherein the component A and the component B are mixed in a ratio of 1:1 and then cured at room temperature; The component A contains at least the following components in parts by mass: 3-6 parts of phenolic epoxy resin, 2-5 parts of epoxy resin, 1-5 parts of core-shell toughened epoxy resin, 3-6 parts of diluent, 0.10-0.20 parts of coupling agent, 0.1-0.5 parts of thixotropic agent, and 75-85 parts of conductive filler; The B component contains at least the following components in parts by mass: 3 to 8 parts of a curing agent and 0.5 to 1.0 parts of an accelerator; Wherein, the core-shell toughened epoxy resin is a bisphenol A type epoxy resin with uniform nano-scale core-shell particle dispersion.
2. A low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The phenolic epoxy resin is EPALLOY-8240, and the epoxy value is 0.57-0.
61.
3. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The epoxy resin is any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and aliphatic epoxy resin, and the epoxy value is 0.40-0.
65.
4. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The core-shell toughened epoxy resin is any one or more of EPX-125, EPX-152, and EPX-252.
5. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The diluent is a mixture of an active diluent and an inactive diluent; Wherein, the active diluent is any one or more of p-tert-butylphenyl glycidyl ether, cyclohexyl dimethanol diglycidyl ether, and trimethylolethane triglycidyl ether; The inactive diluent is any one or more of divalent acid ester, terpineol and benzyl alcohol.
6. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The coupling agent is any one or more of silane coupling agents.
7. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The conductive filler includes flaky silver powder and spherical silver powder; Wherein, the particle size of the flaky silver powder is 1-5 μm, 5-10 μm and 10-15 μm; The particle sizes of the spherical silver powder are 1-5 μm, 5-10 μm and 10-15 μm.
8. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The thixotropic agent is fumed silica.
9. The low temperature curing two-component epoxy resin conductive adhesive according to claim 1, characterized in that: The curing agent is any one or more of the modified amine curing agents EH-451K, HD-2520, and HD-2588; The accelerator is any one or more of DMP-30 and HD-1022.
10. A method for preparing a low temperature curing two-component epoxy resin conductive adhesive according to any one of claims 1 to 9, characterized in that: The steps include: The phenolic epoxy resin, the epoxy resin and the core-shell toughened epoxy resin are mixed evenly, and a vacuum device is used to perform a degassing treatment to obtain a mixed resin; In a grinding state, sequentially adding the thixotropic agent, the diluent, the coupling agent and the conductive filler to the mixed resin, mixing and grinding them to make them fully mixed and uniform, to obtain a first organic carrier; Grinding the first organic carrier to a fineness of 10-30 μm using a three-roll mill to obtain the A component; The curing agent and the accelerator are mixed and ground to be fully mixed, and a vacuum device is used to perform a degassing treatment and then the grinding is continued to obtain a second organic carrier; The second organic carrier is ground to a fineness of 10-30 um using a three-roll mill to obtain the B component.
Citation Information
Patent Citations
Nano-grade-silver-filled room-temperature-cured conductive adhesive
CN102399523A
Cited By
Ultralow-temperature-resistant conductive adhesive and preparation method thereof
CN120041126A